Konsep Klaster pada Tatanan Lahan SMP dan SMA Islam Terpadu - Mochammad Arief Abdul Jabbar; Nareswarananindya Nareswarananindya; Ika Ratniarsih (Tekstur (Jurnal Arsitektur), 2022)
Education is very important for humans in the community. The increase in population can allow for an increase in existing facilities and infrastructure. Merakurak is one of the sub-districts in Tuban Regency with an orbital distance of ± 10 m from the district with an area of 103.77 km. Merakurak District consists of 19 villages with a population of 62,182 with a total of K.K. 18,643. From the data that has been obtained the number of school facilities at the high school level, there are only 2 institutions located in the Merakurak area. The addition of the number of high school education facilities is deemed necessary as a very important educational facility in the future. Responding to population growth, this study aims to provide additional educational facilities and infrastructure for junior and senior high schools in Merakurak sub-district. The arrangement of land arrangements in schools must be designed according to the needs and activities of residents who will be active in it. This educational facility is intended to accommodate teaching and learning activities for children aged 13-18 years. This study uses field research methods and literature with descriptive analysis. The micro-cluster concept in the design of the land arrangement for the Integrated Islamic Middle School and High School is to divide the zones of each building and areas that can be used together. The division of clusters in this concept follows the function of each building such as dividing the middle and high school areas as well as shared areas. The benefit of this design is as an area arrangement for junior and senior high schools with the aim of facilitating students in Merakurak District.